Los medios de comunicación digitales y su desarrollo en la ciudad de Babahoyo - Ortiz Franco, Tatiana Lisbeth (2023)
The growth of digital media in the city of Babahoyo, province of Los Ríos, has been evident during the last decade, due to the development of technology and globalization; Therefore, this study analyzed the way in which local digital media have been developing to remain current within this highly competitive information market. For the development of this research, the quantitative and qualitative method was used, through the technique of survey, interview and observation sheet. To carry out the survey, a sample of 384 inhabitants of the city of Babahoyo was taken into consideration; While to carry out the interview, three digital media managers were applied, while to apply the observation, the media Babahoyo Aldía, Nd Noticias and Click Noticias were examined. The results obtained in this investigation showed that there are currently about 20 native digital media, of which only 7 are in the Public Registry of Media of the Communication Council of Ecuador, where the registration of said media does not ensure greater performance. Since one of the media preferred by the public is not registered, therefore, it is concluded that the strategies applied within the narratives are important for the development of the media and have a better performance in the digital field. Therefore, it was proposed to promote a training workshop aimed at digital media journalists, on the innovation of transmedia narrative, in order to contribute to strengthening the growth of local digital media.